Entrepreneurial mindset: An integrated definition, a review of current insights, and directions for future research. (2nd January 2023) - Daspit, Joshua J.; Fox, Corey J.; Findley, S. Kyle
ABSTRACT: Despite an increasing interest in understanding the mindset of entrepreneurs, little consensus exists on what an entrepreneurial mindset (EM) is, how it is developed, or its precise outcomes. Given the fragmented nature of the multidisciplinary study of EM, we review prior work in an effort to enhance scholarly progress. To this end, we identify and review 61 publications on the topic and offer an empirically derived, integrated definition of EM. Further, we examine factors related to EM and offer specific directions for future study. Additionally, we offer broad directions for advancing the trajectory of EM research and conclude with an abbreviated review of pedagogical insights. In all, by offering a definition, reviewing the literature, and highlighting specific and broad directions for future research, we attempt to consolidate and advance what is known about an individual's EM.